2016
DOI: 10.1017/s0033291716003007
|View full text |Cite
|
Sign up to set email alerts
|

Pervasive influence of maternal and paternal criminal offending on early childhood development: a population data linkage study

Abstract: BackgroundParental criminal offending is an established risk factor for offending among offspring, but little evidence is available indicating the impact of offending on early childhood functioning. We used data from a large Australian population cohort to determine associations between exposure to parental offending and a range of developmental outcomes at age 5 years.MethodMulti-generation data in 66 477 children and their parents from the New South Wales Child Development Study were combined using data link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…Parental antisocial behaviour, for instance, is linked to child externalising problems (Kim, Capaldi, Pears, Kerr, & Owen, 2009;Rhule, McMahon, & Spieker, 2004), and maternal antisocial behaviour is also a risk factor for early childhood physical aggression (Tremblay et al, 2004;Tzoumakis et al, 2017;Tzoumakis, Lussier, & Corrado, 2014). In addition, parental offending has also been shown to be associated with offspring cognitive and internalising problems in early childhood (Coley, Carrano, & Lewin-Bizan, 2011;Laurens et al, 2017), suggesting a more pervasive effect.…”
Section: Introductionmentioning
confidence: 99%
“…Parental antisocial behaviour, for instance, is linked to child externalising problems (Kim, Capaldi, Pears, Kerr, & Owen, 2009;Rhule, McMahon, & Spieker, 2004), and maternal antisocial behaviour is also a risk factor for early childhood physical aggression (Tremblay et al, 2004;Tzoumakis et al, 2017;Tzoumakis, Lussier, & Corrado, 2014). In addition, parental offending has also been shown to be associated with offspring cognitive and internalising problems in early childhood (Coley, Carrano, & Lewin-Bizan, 2011;Laurens et al, 2017), suggesting a more pervasive effect.…”
Section: Introductionmentioning
confidence: 99%
“…More consistent evidence arises from the studies of large, representative cohorts derived from administrative records. Drawing data from a large Australian record linkage project, Laurens et al (2017) found that, after adjustment for socio-demographic covariates, children's risk of poor physical health development at five years of age was highest if their father, mother, or both parents had a history of offending. Greater risk was observed for parents with a history of violent offending, and the magnitude of the association was higher for maternal than paternal offending.…”
Section: Parental Offending and Child Physical Health Problemsmentioning
confidence: 99%
“…However, empirical findings on the effects of parental imprisonment on children have been mixed. Using a population-based record linkage study, two recent Australian studies found associations between parental offending and adverse developmental outcomes in early childhood, including aggression, social competence, language and cognitive skills, and physical health and wellbeing at age five (Laurens et al, 2017;Tzoumakis et al, 2017). On the other hand, an Australian longitudinal study found that, after controlling for pre-existing risk, having a mother whose current partner had ever been incarcerated was not significantly associated with problem behaviors in 14-year-olds (Kinner, Alati, Najman, & Williams, 2007).…”
Section: The Australian Contextmentioning
confidence: 99%